Concurrent measurement of working memory and inhibitory control and their correlations with autistic and ADHD traits in the general population - Yasamin Rahmati; Christopher Jarrold (PLoS ONE, 2026)
Executive function can be defined as the combination of goal representation in working memory and the inhibition of goal-irrelevant responses. This paper comprises two complementary studies that assess these core components of executive function orthogonally and examine their correlation with ASD and ADHD traits in the general population. Both studies utilized a paradigm with two tasks, each assessing working memory and one type of inhibitory control concurrently: the modified flanker task, which measured working memory and interference control, and the modified spatial conflict task, which measured working memory and response inhibition. The aim was to explore the main effects of memory and inhibitory load in each task, investigate potential over-additive interactions between executive function components, and examine the correlations between autistic and ADHD traits and task performance. Each study involved 100 neurotypical adult participants. In Study 1, results showed that reaction time in the flanker task was significantly influenced by demands on both working memory and inhibitory control, whereas in the spatial conflict task only the inhibitory manipulation produced the expected effect. Study 2 introduced modifications that revealed effects on reaction time in the spatial conflict task due to both memory and congruency load. The flanker task demonstrated memory effects in reaction time, but congruency effects were only evident under low memory conditions. No interactions between executive function components in an over-additive way were observed in either Study 1 or Study 2. Bayesian linear regression and correlation analyses found evidence against any meaningful correlations between the size of the congruency or memory effect, computed for any dependent variable and ASC or ADHD traits in both studies.